Effect of Growth Regulators and AgNO3 NPs on the Leaves Extract of Stevia rebaudiana in the Production of Bioactive Compounds in Vitro - Atiyah, Khalid mohsin; Al-Rekaby, Layth Sareea; Musa, Abdulkadhim J. (American Journal of Biology and Natural Sciences, 2026)
The experiment was conducted in the graduate laboratory, Department of biology, College of Science, Al-Qadisiyah University, to study the effect of different concentrations of Clorx on sterilizing explanted on the growth response , and study of the effect of different levels of plant hormones and AgNO3 NPs on the production of active compounds. Used concentrations of (8, 10, and 12%) of Clorx in sterilization explanted where grown in MS medium at a concentration of 4.44 g with sucrose 30 g and agar 7 g and incubated in the growth room at a temperature of 25 °C. The results were recorded after 40 days. The results showed that the response rate of the growths was higher at a concentration of 10%, and this percentage was ideal for sterilization, as the response rate was recorded. 72%, while the contamination rate in the samples was 12 %, while the chlorine concentration was 8%, it recorded a growth rate of 78%, but the contamination rate was high if it was recorded at 28%, while the concentration was 12%, the growth response rate was low, as it was recorded at 48% and the contamination rate was 10%. Plant Growth Regulators and AgNO3 nanoparticles were added to the medium at different concentrations. The results of the GC-MS analysis showed a group of compounds of medical importance, including n-Hexadecanoic acid, Octadecanoic acid, Cycloheptasiloxane, Diethyl Phthalate, Phytol, and Propanoic acid. The The compounds n-Hexadecanoic acid, Octadecanoic Acid, and Cycloheptasiloxane showed the highest ratio in the treatment (4 NAA, 2 Kin, 3 AgNO3 NPs), while the compound Diethyl Phthalate achieved the highest ratio in the treatment (2 NAA, 1 Kin, 6 AgNO3 NPs). The compound Phytol showed the highest ratio in the treatment (2 NAA, 1 Kin, 0 AgNO3 NPs), and the highest ratio for the compound Propanoic acid was observed in the treatment (4 NAA, 2 Kin, 6 AgNO3 NPs).